Evaluasi Desain Bejana Bertekanan pada Radiator Cooling System Menggunakan Material SPCC-SD - Sukarman, Sukarman; Khoirudin, Khoirudin; Murtalim, Murtalim; Mulyadi, Dodi; Rahdiana, Nana (Rekayasa, 2021)
This study discusses the analysis of a pressure vessel's design in the Radiator Cooling 1000 (RC-1000) system, which operates at a design temperature of 110oC. A pressure vessel is a container of gaseous, solid, or liquid material subjected to internal or external pressure and can withstand various other load variations. The pressure vessel on the RC-1000 system has a outer diameter of 87.8 mm or 3.46 inches and will experience an internal pressure of about 20.84 psi or 143.7 kPa, so it must be designed safely. This research method uses analytical and experimental methods. The analytical method is used to calculate the thickness of the pressure vessel material, the maximum allowable working pressure, and the hydrostatic test calculation. While the experimental method was carried out on the hydrostatic test process, the evaluation was based on the prevailing regulations in the Republic of Indonesia. Using the SPCC-SD material (JIS 3141), it was found that the minimum thickness of this pressure vessel is 0.0453 inches on the shell side and 0.0435 inches on the head/head side. The thickness of the material used on the shell side and head/head is 0.0472 inches in practice. This pressure vessel has passed the hydrostatic test at 232.1 psi or 1600 kPa.